Place Of Creation And Place Of Production: Spatial Dimensions Of The Berlin Fashion-Design Production Network - Copercini, Marco (Quaestiones Geographicae, 2015)
Fashion design plays a significant role in Berlin’s creative industries and for its start-up scene. Berlin has the highest concentration of designers in Germany, most of them working in small start-ups, while the spatial organisation of their production is stretched from the local level to the global network of fashion events, showing different entrepreneurial strategies within the production process. Different spatial structures of the production organisation are identifiable through which it is possible to discuss the role of Berlin in the production network of fashion designers and the kinds of relations holding between the city, designers, and their production network.